Effect of cycling shoe cleat position on biomechanical and physiological responses during cycling and subsequent running parts of a simulated Sprint triathlon: a pilot study - Millour, G.; Janson, L.; Duc, S.; Puel, F.; Bertucci, W. (Journal of Science and Cycling, 2020)
Proper cleat adjustment improves cycling performance and prevents knee injuries. Recommendations have included positioning the first metatarsal head above the pedal spindle or slightly forward, but mid-foot cleat positions could be more appropriate in triathlons at constant load for their impact on the subsequent running performance. We evaluated the impact of antero-posterior cleat position on biomechanical and physiological variables during the cycling and running parts of a simulated Sprint triathlon. Seven participants performed two 32-min cycling tests including 8 sets of 3 min 30 s intervals performed at just below the power output at the first ventilatory threshold interspersed with 30 s sprints at > 100% of the maximal aerobic power. The cycling exercises were immediately followed by a maximal running performance of 20 min. The tests were performed with a 5-mm backward (BCP) and a 5-mm forward (FCP) first metatarsal cleat position. The BCP decreased the energetic cost during running (5.9%; p = 0.04; effect size [ES] = 0.92) despite no significant performance change in the cycling or the subsequent running tests. Moreover, the BCP resulted in a lower soleus recruitment during sub-maximal intensity (7.0%; p < 0.05; ES = 1.23) and of the gastrocnemius medialis (25.0%; ES = 1.00; p < 0.05) and tibialis anterior (11.9%; ES = 1.51) during the subsequent running. However, we observed much higher recruitment of the soleus (8.8%; ES = 1.36), vastus lateralis (10.1%; ES = 1.37), biceps femoris (12.0%; ES = 1.45), tibialis anterior (16.4%; ES = 3.35), and overall lower limb (11%; ES = 0.92) during sprints with the BCP. Therefore, the BCP could be more suitable in triathlons by being more economical for subsequent running despite the greater muscle activity during the cycling sprints, which form an important part of the cycling portion of Sprint triathlons.